Neural injury after use of vasopressin and adrenaline during porcine cardiopulmonary resuscitation. (March 2015) - Halvorsen, Peter; Sharma, Hari Shanker; Basu, Samar; Wiklund, Lars
Abstract Background. Our aim was to investigate cerebral and cardiac tissue injury subsequent to use of vasopressin and adrenaline in combination compared with vasopressin alone during cardiopulmonary resuscitation (CPR). Methods. In a randomized, prospective, laboratory animal study 28 anesthetized piglets were subject to a 12-min untreated cardiac arrest and subsequent CPR. After 1 min of CPR, 10 of the piglets received 0.4 U/kg of arg8-vasopressin (V group), and 10 piglets received 0.4 U/kg of arg8-vasopressin, 1 min later followed by 20 µg/kg body weight of adrenaline, and another 1 min later continuous administration (10 µg/kg/min) of adrenaline (VA group). After 8 min of CPR, the piglets were defibrillated and monitored for another 3 h. Then they were killed and the brain immediately removed pending histological analysis. Results. During CPR, the VA group had higher mean blood pressure and cerebral cortical blood flow (CCBF) but similar coronary perfusion pressure. After restoration of spontaneous circulation there was no difference in the pressure variables, but CCBF tended to be (36% ± 16%) higher in the V group. Neuronal injury and signs of a disrupted blood–brain barrier (BBB) were greater, 20% ± 4% and 21% ± 4%, respectively, in the VA group. In a background study of repeated single doses of adrenaline every third minute after 5 min arrest but otherwise the same protocol, histological measurements showed even worse neural injury and disruption of the BBB. Conclusion. Combined use of vasopressin and adrenaline caused greater signs of cerebral and cardiac injury than use of vasopressin alone during experimental cardiopulmonary resuscitation.